Implementasi Ajaran Raja Marga Yoga Dalam Mengembangkan Kepribadian Dan Kesehatan Jasmani Masyarakat Hindu di Kota Palangka Raya - Sukiada, Kadek; Wiwekananda, Satya (Jurnal Penelitian Agama Hindu, 2024)
The Hindu community in Palangkaraya City can improve health holistically by integrating physical, mental, and spiritual health by practicing the teachings of Raja Marga Yoga. The practice of Raja Marga Yoga can be used to promote public health and personal development in the integration of Hindu community culture, which has its own uniqueness. This research aims to find out and inform about the forms, obstacles, and efforts to implement Raja Marga Yoga teachings so that these teachings can be used as a reference for the Hindu community in Palangka Raya City. This research uses a descriptive qualitative method that describes the unique results of the Raja Marga Yoga program by looking at forms, obstacles, and efforts as an analytical tool. The findings of this research indicate that the Hindu community in Palangka Raya City is implementing the Raja Marga Yoga Program in several implementation stages, namely the timing stage. Meditation stage, and surya namaskar yoga movement stage. Implementation of the teachings of Raja Marga Yoga can not only develop personality through efforts to apply the teachings of yama and nyama brata, but it also seeks to provide physical health through efforts to apply asana, pranayama, dhyana, dharana, meditation, samadhi and Patanjali's Yoga Sutra (Surya Namaskar). The implementation of Raja Marga Yoga teachings in Palangka Raya City is a distinctive characteristic of the Hindu community in this city. It is different from Hindu communities in other cities.